Latitudinal shift in the timing of flowering of tree species across tropical Africa: Insights from field observations and herbarium collections - (:unkn) unknown (My University, 2020)
Temporal and spatial patterns in flowering phenology were assessed for eight tropical Africantree species. Specifically, the frequency and seasonality of flowering at seven sites in central Africawere determined using field data, graphical analysis and circular statistics. Additionally, spatialvariation in the timing of flowering across species range was investigated using herbarium data,analysing the relative influence of latitude, longitude and timing of the dry season with aBayesian circular generalized linear model. Annual flowering was found for 20 out of the 25 pop-ulations studied. For 21 populations located at the north of the climatic hinge flowering wasoccurring during the dry season. The analysis of herbarium collections revealed a significant shiftin the timing of flowering with latitude forE. suaveolens, and with the timing of the dry season forM. excelsa(and to a lesser extentL. alata), with the coexistence of two flowering peaks near theequator where the distribution of monthly rainfall is bimodal. For the other species, none of latitude,longitude or timing of the dry season had an effecton the timing of flowering. Our study highlightsthe need to identify the drivers of the flowering phenology of economically important African treespecies.
Keywords: African Research